ANALISIS HUKUM PROSES PENGAMBILALIHAN SAHAM ANAK PERUSAHAAN PT KRAKATAU STEEL TBK OLEH PT CHANDRA ASRI PETROCHEMICAL TBK MELALUI PERJANJIAN JUAL BELI SAHAM BERSYARAT - Feridha Medina Hidayat; Tamarine Camalia; Katya Benalda; Lina Budiarti; Desti Rahpriangan; Fatma Namira Maudya (LPPM Universitas Ekasakti Padang, 2023)
Acquisition (takeover) can be one of the company's development strategies for the economic interests of each takeover company or company that is taken over, one way of acquisition is carried out through a share sale and purchase agreement, either all or most of the company's shares which results in the transfer of control of the company. In this case, it will be reviewed regarding the acquisition made by a subsidiary of PT Krakatau Steel with PT Chandra Asri Petrochemical in accordance with applicable regulations. The purpose of this writing is to find out how the acquisition process occurred at PT Krakatau Steel with PT Chandra Asri Petrochemical. Next to find out what legal consequences occur after the acquisition. The research method used in this study is normative juridical, which is based on positive legal rules or norms through the relevant legislation. The research specification used is descriptive analysis, which is carried out by analyzing and describing completely and thoroughly which is associated with legal theory regarding the process and legal consequences of the acquisitions made by the two companies above. Based on the writing, it was obtained: First, the acquisition made between Krakatau's subsidiary and CAP is categorized as a vertical acquisition with the aim of strengthening the supply chain of business fields carried out by CAP. Then the process of acquiring shares carried out by CAP against KSI through its subsidiaries, namely KTI and KDL is by purchasing shares in each company as stated in the Deed of Takeover. Second, due to the law of the acquisition of PT Krakatau Daya Listrik and PT Krakatau Tirta Industry by PT Chandra Asri Petrochemical Tbk is a change in control of PT Krakatau Daya Listrik company by PT Chandra Asri Petrochemical, changes in shareholder composition, as well as the obligation to report material information to OJK and the public as well as notification to KPPU regarding the takeover. Acquisitions can also have an effect on the company's structure and workforce structure.